2009
DOI: 10.1002/fld.2170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat transfer on the flow of a second‐grade fluid in divergent/convergent channel

Abstract: SUMMARYThis paper studies the effects of a second-grade fluid on the flow and heat transfer characteristics in a divergent/convergent channel. The momentum and energy equations are first given in a nondimensional form and then solved analytically using the method of homotopy analysis method. Convergence of derived series solutions is shown. Graphical results for the velocity and the temperatures are presented and discussed for various emerging parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Besides, in Figure 2, for verification, the results for a special case (Ha=0, De=0.8, Re=40, and α=5 o ) is plotted and compared with the that of Ref. [12]. It can be seen that there is good agreement between th two.…”
Section: 1 Numerical Methodsmentioning
confidence: 60%
See 1 more Smart Citation
“…Besides, in Figure 2, for verification, the results for a special case (Ha=0, De=0.8, Re=40, and α=5 o ) is plotted and compared with the that of Ref. [12]. It can be seen that there is good agreement between th two.…”
Section: 1 Numerical Methodsmentioning
confidence: 60%
“…The results showed that the maximum velocity is obtained in the middle section of the divergent channel. Hayat et al [12] studied the effects of a second-grade fluid flow in a divergent channel, and showed that the dimensionless velocity is a function of Reynolds number and divergent angle which reduces the velocity. However, when Deborah number increases, the velocity is also increased.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this fact in recent years, the study of viscoelastic fluids gains considerable attention of researchers working in this area. Some important investigations reflecting the viscoelastic effects are presented by [30][31][32][33][34][35][36]. Heat transfer in viscoelastic fluids due to boundary-layer in the presence of thermal radiations and constant suction is discussed by [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Change in angle plays an important role in these flows as discussed in various studies. The work for non-Newtonian nature of the fluid has been presented by Hayat et al 9 and Asadullah et al 10 Some other related studies are available in open literature [11][12][13][14] and references therein. Nanofluids, as the name suggests, are the suspensions of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%